WARISAN KERAJAAN PAGARUYUNG: Studi Historis-Antropologis - Rahmawati, Nadia; Susanti, Lr Retno; Hudaidah (Universitas Banda Naira, 2024)
The relics of the Pagaruyung Kingdom are a very valuable cultural heritage for the Minangkabau people in West Sumatra. This article discusses the history and cultural contributions offered by this kingdom, with an emphasis on historical artifacts and buildings, especially the Pagaruyung Palace which reflects the uniqueness of traditional architecture. Through a historical and anthropological analysis approach, this study identifies the social, economic and spiritual values contained in these relics. Apart from that, this article also Keywords: Minangkabau Culture, Pagaruyung Kingdom, Royal Legacy examines the challenges faced in preserving cultural heritage in modern times, as well as the importance of joint efforts to maintain Minangkabau cultural identity. Thus, this research aims to increase awareness regarding the importance of preserving cultural heritage as part of Indonesia's cultural diversity